2001
DOI: 10.1111/j.1365-3032.2001.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects on growth, reproduction, body composition and stress resistance in the terrestrial isopodsOniscus asellusandPorcellio scaber

Abstract: The effect of differences in food composition on growth, body composition and cold tolerance of the isopods Porcellio scaber (Latreille) and Oniscus asellus (L.) has been studied. The effect on reproduction of P. scaber was included. Total lipid and protein content remained the same in O. asellus, given food with a nitrogen content of 2.4, 2.5, 2.8 or 3.1% for 8 weeks. Those fed on 3.1% N gained signi®cantly more weight than those fed on 2.4, 2.5 or 2.8% N. Cold tolerance after a period of low temperature accl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Since ter restrial isopods mainly feed on food sources that are considered to be low quality, it is obvious that biological aspects further depend on the available food source (Zimmer & Topp 2000). Some authors have used different leaf species and diets to examine the influence of leaf litter attributes (e.g., nitrogen (N) content, phenolics, colonizing microbiota, acidity, pH) on isopods (Merrian 1971, Rushton & Hassall 1983, 1987, Danger field 1989, Hassall & Dangerfi eld 1990, Zimmer & Topp 1997, 2000, Kautz et al 2000, Lavy et al 2001, Zimmer 2002, 2003, Lardies et al 2004). These works demonstrated that the vegetable composition af fects the isopod biology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ter restrial isopods mainly feed on food sources that are considered to be low quality, it is obvious that biological aspects further depend on the available food source (Zimmer & Topp 2000). Some authors have used different leaf species and diets to examine the influence of leaf litter attributes (e.g., nitrogen (N) content, phenolics, colonizing microbiota, acidity, pH) on isopods (Merrian 1971, Rushton & Hassall 1983, 1987, Danger field 1989, Hassall & Dangerfi eld 1990, Zimmer & Topp 1997, 2000, Kautz et al 2000, Lavy et al 2001, Zimmer 2002, 2003, Lardies et al 2004). These works demonstrated that the vegetable composition af fects the isopod biology.…”
Section: Introductionmentioning
confidence: 99%
“…The feeding activities of woodlice speed up the decomposition process and help return essential nutrients to the soil (Hopkin 1991, Wolters & Ekschmitt 1997. This species like other terrestrial isopods is considered a generalist decomposer, feeding mainly on dead plant material (Paris & Pitelka 1962, Warburg 1993, Wolters & Ekschmitt 1997, Lavy et al 2001, Zimmer 2004. In most terrestrial ecosystems, an over whelming par t of the above-ground biomass produced by plants is recycled by the decomposition process of leaf litter caused by saprophagous soil animals and microorganisms (Swift et al 1979cited by Zimmer & Topp 1997.…”
Section: Introductionmentioning
confidence: 99%
“…This observation might hint, together with the slightly, not statistically significant, better performance of L. terrestris when feeding on GE wheat, to a feeding activity more triggered by the nutritional value of the crop varieties. Earthworms might adapt the amount of consumption to the quality of food as a pre-ingestive compensatory mechanism (Lavy et al, 2001). However, a chemical analysis of the structural plant components (Lindfeld et al 2010) did not find significant differences between GE wheat and non-GE wheat and the regression analysis showed no correlation between structural plant components or C/N ratio and the amount of litter consumption, respectively weight change of L. terrestris.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, we could not measure other key traits, such as growth rate and offspring number, but it is likely that they show plasticity across hosts as well. Life-history traits of isopods are strongly affected by abiotic conditions such as diet (Lavy et al, 2001), temperature and moisture (Dixie, White, & Hassall, 2015). For example the isopods Armadillidium vulgare and Idotea baltica have, respectively, a faster growth rate and a larger size in patches with highquality food (Hassall, Helden & Benton, 2003;Hemmi & Jormalainen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Body size is an environmentally plastic trait in isopods, which is easy to measure and is strongly positively correlated with fecundity (e.g. Lavy et al, 2001;Hemmi & Jormalainen, 2004). Sex ratio has a strong effect on population dynamics and mating strategies and might also be affected by the environment in isopods (Rigaud et al, 1997).…”
Section: Introductionmentioning
confidence: 99%